THE EFFECT OF CHEMICALS ON PRODUCTIVITY AND QUALITY OF OATS IN THE CONDITIONS OF RADIOACTIVE POLLUTION - V. F. Shapovalov; N. M. Belous; G. P. Malyavko; L. Р. Kharkevich (Зерновое хозяйство России, 2018)
Novozybkovskaya Agricultural Station ARRI of RAA carried out long-term trials in the four-field crop rotation, started in 1993, on the radioactive polluted sod-podzolic loose sandy soils. It studied the effects of different fertilizers used both separately and together with pesticides and the growth regulator ‘Gumistim’ on productivity and quality of oats grain. An effective fertilizing system, which promotes stable productivity and high quality of grain in the conditions of radioactive pollution, has been found. The highest productivity (2.79 t/ha) was obtained after application of organic-mineral fertilizing system together with pesticides and the growth regulator ‘Gumistim’. The contents of raw protein in oats grain varied to a greater extent due to meteorological conditions during the vegetation period and to a lesser extent due to intensification of the fertilizing system. On average during the years of study the index was rather high (10.07-13.89%). The studied fertilizing systems, used both separately and together with other chemicals, promoted the increase of protein in oats grain. Under the influence of chemicals the biochemical composition of oats has improved. The contents of raw fat in grain varied from 3.55 to 4.40%, raw ash from 2.6 to 3.2%, sugar from 3.1 to 4.8%, starch from 52.8 to 53.8%, the contents of raw fiber decreased from 11.06 to 9.31%. Organic-mineral and mineral fertilizing systems (N110P40K100) together with pesticides and the growth regulator ‘Gumistim’ promote the increase of essential amino acids in grain. Organic and mineral fertilizers decreased the contents of 137Cs (taken from soil) in the yield of oats grain. The decrease of the level of 137Cs to the normal was noticed after the complex application of chemicals. The mineral fertilizing system together with the means of plant protection and the fertilizer (N165P60K150 + ‘Gumistim’) gave the largest reduce of the 137Cs concentration.